Analisis Willingness to Pay (WTP) Peserta BPJS Kesehatan Dengan Pendekatan Contingent Valuation Method - Khoiri, Abu; Sandra, Christyana; Putra, Dewa Ngakan Gde Wahyu Mahatma; Herawati, Yennike Tri (Puslitbang Sinergis Asa Professional, 2025)
The increasing number of Social Security Agency of Health (BPJS Kesehatan) participants who are inactive or drop out be a threat to participation in the health insurance program in Indonesia. Inactive participants in August 2022 recorded 45,987,956. The most common cause is not paying premiums according to applicable regulations. The purpose of the research is to analyze the factors that influence the willingness to pay for BPJS Kesehatan participants using the contingent valuation method approach. This research used quantitative methods with an analytic observational approach through surveys. The unit of analysis in research was the individual. The reachable population for the study were BPJS Kesehatan participants in the category of non-Recipients of Contribution Assistance (non-PBI) in the BPJS Kesehatan Jember working area (Jember and Lumajang Regencies). The sample size was 167 respondents taken using the quota sampling technique. Data analysis with multiple linear regression. The results showed that the Perceived Benefit Package, Perceived Sacrifice, and Free Mentality contributed to the formation of willingness to pay premiums regularly. Only the Conformity Effect does not significantly contribute of willingness to pay premiums regularly. Perceived Sacrifice and Free Mentality contribute in opposite directions. This means that if the respondent's Perceived Sacrifice and Free Mentality are high, it will affect the low willingness to pay premiums. It is necessary to develop a program that can provide added value for Non-PBI participants who so far rarely or have never used health services. This aims to maintain the motivation of participants to remain willing to pay premiums regularly.